Impact of Online Science Learning on Children Aged 5-6 During the COVID-19 Pandemic: A Case Study at Barunawati Kindergarten 3 Samarinda: Dampak Pembelajaran Sains Secara Online pada Anak Usia 5-6 Tahun selama Pandemi COVID-19: Studi Kasus di TK Barunawati 3 Samarinda - Evie Palenewen; Tamara Dewi Audiya; Fachrul Rozie (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2023)
The objective of this research is to provide a depiction of the effects of online science education on children between the ages of 5 and 6 amidst the COVID-19 pandemic, specifically in relation to the development of science learning abilities in this age group. This research aims to investigate the challenges and barriers encountered during the execution of science education for children aged 5–6 years at Barunawati 3 Samarinda Kindergarten. The research employs a case study methodology, which centers on the individuals involved in a particular teacher's online science learning case, as a means of adapting to crisis situations. The Barunawati 3 Samarinda Kindergarten has been accredited as